2019
DOI: 10.1002/jcb.28846
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolite biomarkers related to secondary hyperparathyroidism and parathyroid hormone

Abstract: Background Hyperphosphatemia, hypocalcemia, and elevation of parathyroid hormone (PTH) are typical abnormalities of uremic patients with Secondary hyperparathyroidism (SHPT). However, metabolic imbalance associated with SHPT is not well understood. Methods A total of 15 SHPT patients with an intact parathyroid hormone (iPTH) level > 600 pg/mL were set as preoperative (PR) group, 15 age‐ and gender‐matched controls who had undergone parathyroidectomy plus forearm transplantation because of hyperparathyroidism a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Furthermore, the results suggest that metabolic pathway patterns also shift, involving routes of protein synthesis, amino acid metabolism, and steroid hormone metabolism in addition to the established metabolic pathways associated with phosphorus, calcium, PTH, and vitamin D (Levin et al, 2007), with evident promise for better understanding of the pathogenesis in CKD-MBD. Another similar article performed by Shen et al (2019) also found various biomarkers correlated to PTH in SHPT. However, in contrast to the above study, which mainly focused on the altered metabolites in CKD-MBD, this study primarily focused on those correlated with PTH.…”
Section: Proteomics/metabolomics Studies On Ckd-mbdmentioning
confidence: 68%
See 2 more Smart Citations
“…Furthermore, the results suggest that metabolic pathway patterns also shift, involving routes of protein synthesis, amino acid metabolism, and steroid hormone metabolism in addition to the established metabolic pathways associated with phosphorus, calcium, PTH, and vitamin D (Levin et al, 2007), with evident promise for better understanding of the pathogenesis in CKD-MBD. Another similar article performed by Shen et al (2019) also found various biomarkers correlated to PTH in SHPT. However, in contrast to the above study, which mainly focused on the altered metabolites in CKD-MBD, this study primarily focused on those correlated with PTH.…”
Section: Proteomics/metabolomics Studies On Ckd-mbdmentioning
confidence: 68%
“…Another similar article performed by Shen et al (2019) also found various biomarkers correlated to PTH in SHPT. However, in contrast to the above study, which mainly focused on the altered metabolites in CKD-MBD, this study primarily focused on those correlated with PTH.…”
Section: Proteomics/metabolomics Studies On Ckd-mbdmentioning
confidence: 68%
See 1 more Smart Citation
“…Pruritus is an unpleasant feeling associated with the urge to scratch; it is a subjective symptom that is caused by many factors and has multiple dimensions [4]. The causes of skin pruritus in patients with SHPT may be related to the increase in parathyroid hormone (PTH), hyperphosphatemia and the accumulation of some medium and large molecular toxins, such as β2-mg, in vivo [5]. Parathyroidectomy (PTX) is the main treatment at present and might also reduce calcium-phosphorus product concentrations, PTH and in ammatory factors, thus controlling vascular calci cation and relieving bone pain and skin pruritus [6].…”
Section: Introductionmentioning
confidence: 99%
“…Pruritus is an unpleasant feeling associated with the urge to scratch; it is a subjective symptom that is caused by many factors and has multiple dimensions [4]. The causes of skin pruritus in patients with SHPT may be related to the increase in parathyroid hormone (PTH), hyperphosphatemia and the accumulation of some medium and large molecular toxins, such as β2-mg, in vivo [5]. Parathyroidectomy (PTX) is the main treatment at present and might also reduce calcium-phosphorus product concentrations, PTH and inflammatory factors, thus controlling vascular calcification and relieving bone pain and skin pruritus [6].…”
Section: Introductionmentioning
confidence: 99%